2016
DOI: 10.1371/journal.pntd.0004387
|View full text |Cite
|
Sign up to set email alerts
|

A Sero-epidemiological Approach to Explore Transmission of Mycobacterium ulcerans

Abstract: The debilitating skin disease Buruli ulcer (BU) is caused by infection with Mycobacterium ulcerans. While various hypotheses on potential reservoirs and vectors of M. ulcerans exist, the mode of transmission has remained unclear. Epidemiological studies have indicated that children below the age of four are less exposed to the pathogen and at lower risk of developing BU than older children. In the present study we compared the age at which children begin to develop antibody responses against M. ulcerans with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…All of the studied communities along the Offin River basin were designated endemic; the communities included Ntobroso and Achiase in the Atwima district, upstream and midstream of the river, respectively, and Mfantsiman in the Upper Denkyira district, downstream of the river. Extensive seroepidemiological studies (34)(35)(36) conducted in these communities indicated high levels of serological evidence of exposure of community members to M. ulcerans 18-kDa small heat shock protein (hsp) (33), irrespective of the disease burden.…”
Section: Methodsmentioning
confidence: 99%
“…All of the studied communities along the Offin River basin were designated endemic; the communities included Ntobroso and Achiase in the Atwima district, upstream and midstream of the river, respectively, and Mfantsiman in the Upper Denkyira district, downstream of the river. Extensive seroepidemiological studies (34)(35)(36) conducted in these communities indicated high levels of serological evidence of exposure of community members to M. ulcerans 18-kDa small heat shock protein (hsp) (33), irrespective of the disease burden.…”
Section: Methodsmentioning
confidence: 99%
“…The highest detection rates were found sometimes in 75-to 79-year-old patients in West Africa, probably due to the reactivation of disease from a latent infection of M. ulcerans (380). It was proven in Africa that children less than 5 years old rarely develop antibody responses to the 18-kDa small heat shock protein (shsp) of M. ulcerans and thus seem to be considerably less exposed to the pathogen than older children (381,382). As Buruli ulcer is not known to be an immunizing infection, this may reflect a greater exposition to sources and vectors (381,382).…”
Section: Descriptive Epidemiology Of Buruli Ulcermentioning
confidence: 99%
“…However, this antigen is not suitable as target for a BU-specific serological test, as anti-shsp antibodies are also frequently found in sera of healthy individuals living in BU endemic areas [75]. This circumstance however has opened up the opportunity for seroepidemiological studies assessing the exposure of populations to M. ulcerans [76][77][78].…”
Section: Serological Tests: Only Suitable For Seroepidemiological Stumentioning
confidence: 99%